Is being a victim of bullying or cyberbullying in secondary school associated with subsequent risk‐taking behavior in adolescence? A longitudinal study in secondary schools. Issue 4 (28th April 2022) - Shah, R.; Dodd, M.; Allen, E.; Viner, R.; Bonell, C.
Abstract: Introduction: Neurobiological and social changes in adolescence can make victims of bullying more susceptible to subsequent impulsive behavior. With the high prevalence of bullying in schools and rise in cyberbullying in the United Kingdom, it is important that the health impacts of bullying victimization, including on risk‐taking, are understood. Our study aims to investigate whether bullying/cyberbullying victimization is associated with subsequent health risk‐taking behavior in adolescence. Risk‐taking behavior includes electronic cigarette and cigarette smoking, alcohol consumption, illicit drug use, early sexual debut, weapon carrying, damaging property, and setting fire. Methods: A secondary quantitative analysis of data from 3337, English, secondary school students in the control arm of the INCLUSIVE trial, constituting an observational cohort. Bullying victimization was measured at baseline (age 11/12 years) using the gatehouse bullying scale and a separate question on cyberbullying victimization. Logistic regression was used to test for an association between bullying/cyberbullying victimization at baseline and risk‐taking behavior at 36 months, adjusting for baseline risk‐taking behavior and other potential confounders, and accounting for school clustering. Results: There was strong evidence ( p  ≤ .02) for a positive dose‐responsive association between being bullied at baseline and nearly all risk‐taking behavior at follow‐up. Although there was no evidence for an association between being bullied at baseline and weapon carrying ( p  = .102), there was evidence for a positive association between being cyberbullied at baseline and weapon carrying ( p  = .036). Conclusions: It is plausible that bullying/cyberbullying victimization increases the likelihood of subsequent risk‐taking behavior in adolescence. Policy options should focus on implementing evidence‐based antibullying school interventions.